An analysis of Japanese stock return dynamics conditional on U.S. Monday holiday closures - Takato Hiraki; Edwin D. Maberly (Federal Reserve Bank of Atlanta, 2000)
This paper examines a unique data set consisting of Japanese equity returns for the Friday, Monday, and Tuesday surrounding U.S. Monday holiday closures. The objective is to neutralize the impact of spillover effects from New York to Tokyo. Prior studies find that Japanese returns are negative on Tuesday and anomalous; this phenomenon is known as the Japanese-Tuesday effect. One explanation for the Japanese-Tuesday effect is that there exists a cause and effect relationship with Monday returns in New York. Historically, Monday returns in New York are negative, a phenomenon known as the U.S.-Monday effect. The empirical results show that U.S. Monday closures have a significant impact on Japanese return dynamics for surrounding trading days. The empirical evidence does not support the hypothesis that the U.S.-Monday and Japanese-Tuesday effects are related. Potential explanations for the occurrence and then disappearance of the Japanese-Tuesday effect rely on microstructure properties unique to Tokyo. More recently, spillover effects from New York to Tokyo have increased in intensity, and this is attributed to the introduction of the Nikkei 225 index on the SIMEX.
Keywords: 330; Financial markets; International finance; Japan; Stock market